2015
DOI: 10.1159/000433557
|View full text |Cite
|
Sign up to set email alerts
|

Opening of a Respiratory Intermediate Care Unit in a General Hospital: Impact on Mortality and Other Outcomes

Abstract: Background: Respiratory intermediate care units (RICUs) are specialized areas aimed at optimizing the cost-benefit ratio of care. No data exist about the impact of opening a RICU on hospital outcomes. Objectives: We wondered if opening a RICU may improve the outcomes of patients with acute respiratory failure (ARF), acute exacerbation of chronic obstructive pulmonary disease (AECOPD), or community-acquired pneumonia (CAP). Methods: We analyzed the discharge abstracts of 2,372 admissions to the RICU and interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
(38 reference statements)
1
18
0
4
Order By: Relevance
“…Also recently, respiratory intermediate care units (RICUs) can provide an effective NIV application to patients have been introduced in Europe (31). Moreover, RICUs have the advantages to reduce hospital mortality, need for ICU admission, and hospital stay (32). In the present study, NIV was used more in the ICU group than ward group (data was not shown).…”
Section: Discussionmentioning
confidence: 55%
“…Also recently, respiratory intermediate care units (RICUs) can provide an effective NIV application to patients have been introduced in Europe (31). Moreover, RICUs have the advantages to reduce hospital mortality, need for ICU admission, and hospital stay (32). In the present study, NIV was used more in the ICU group than ward group (data was not shown).…”
Section: Discussionmentioning
confidence: 55%
“…Little formal investigation exists to describe and evaluate the effectiveness of PCUs ( 3 ). It is hypothesized that ICU services, bed utilization, and patient care outcomes may be positively impacted through use of PCUs ( 4 , 33 35 ); similarly Tele-ICU has shown to impact these factors positively ( 10 , 11 , 13 15 , 36 ) and therefore, Tele-PCU may also provide a distinct advantage. We found that PCU and hospital mortality rates were significantly lower for patients in TPCU group, compared with patients in NTPCUs.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing RICUs in general hospitals has been found to reduce in-hospital mortality and LOS of subjects with acute respiratory diseases. 20 The pathway of admission in a RICU is a major determinant of patient outcomes. 21 It may be classified as follows: step-down pathway, which corresponds to an admission from an ICU; step-up pathway, which corresponds to an admission from a hospital ward; or direct pathway, which corresponds to an admission from the emergency department.…”
Section: Discussionmentioning
confidence: 99%